PENGARUH PENGGUNAAN STRATEGI PEMBELAJARAN THINK TALK WRITE (TTW) TERHADAP HASIL BELAJAR SISWA PADA MATERI BUNYI KELAS VIII MTs NEGERI BATANG ANGKOLA - Lia Purnama Sari (JURNAL PhysEdu (PHYSICS EDUCATION), 2024)
This study aims to find out the description of the use of Think Talk Write learning strategy in class VIII MTs NegeriBatangAngkola, to know the students' learning outcomes before and after the sound material using Think Talk Write strategy in class VIII MTs NegeriBatangAngkola, and to know the influence that Significance between Think Talk Write Learning Strategy to physics student learning result of Beep in class VIII MTs NegeriBatangAngkola. The method used in this research is experimental method. The population in this study is all students of class VIII MTs NegeriBatangAngkola consisting of 4 classes, amounting to 118 students. The sampling technique used is random sampling technique. So researchers only take one sample from class VIII-4 that amounted to 30 students. Based on the results of calculations on statistical analysis illustrates that the average value of the use of Think Talk Learning Learning Strategy on Sound Material in Grade VIII MTs NegeriBatangAngkola 3.5 with the category of "Very Good", while the results of student learning on sound material before the use of learning Think Talk Write obtained an average score of 38 with the category "Failed", and after the use of Think Talk Write learning obtained an average value of 81 with the category of "Very Good". In order to know the hypothesis that is enforced in this study accepted or rejected, then conducted inferential analysis by using the formula "t-test". From the results of research, the t-value is greater than t-table (23.06> 1.70). That means the alternative hypothesis enforced in this study can be accepted.